Septuagint, Targum and beyond: comparing Aramaic and Greek versions from Jewish antiquity - Shepherd, David; Joosten, Jan; Meer, Michaël N. van der (Supplements to the Journal for the study of Judaism, 2020)
"In Septuagint, Targum and Beyond leading experts in the fields of biblical textual criticism and reception history explore the relationship between the two major Jewish translation traditions of the Hebrew Bible. In comparing these Greek and Aramaic versions from Jewish antiquity the essays collected here not only tackle the questions of mutual influence and common exegetical traditions, but also move beyond questions of direct dependence, applying insights from modern translation studies and comparing corpora beyond the Old Greek and Targum, including, for instance, Greek and Aramaic translations found at Qumran, the Samareitikon, and later Greek versions."